Time‐Dependent Freshwater Input From Ice Shelves: Impacts on Antarctic Sea Ice and the Southern Ocean in an Earth System Model. Issue 20 (25th October 2017) - Pauling, Andrew G.; Smith, Inga J.; Langhorne, Patricia J.; Bitz, Cecilia M.
Abstract: Earth System Models do not reproduce the observed increase in Antarctic sea ice extent which may be due to the unrealistic representation of ice shelves. Here we investigate the response of sea ice to increasing freshwater input from ice shelves using the Community Earth System Model with the Community Atmosphere Model version 5 [CESM1(CAM5)]. We have conducted model experiments adding fresh water as if from ice shelf melt with a linear increase in the rate of input over the period 1980–2013. Including the effect of heat loss from the ocean to melt ice shelves resulted in significantly more positive trends in sea ice area. We found that an increase in the rate of change of freshwater input of ∼45 Gt yr −2 was sufficient to offset the negative trend in sea ice area in CESM1(CAM5), although the freshwater input by the end of the experiment was larger than observed at that time. Key Points: Modeled Antarctic sea ice area decrease reversed with linearly increasing freshwater forcing: more positive trends when latent heat included Increase in the rate of change of freshwater input of ∼45 Gt yr ‐2 sufficient to offset modeled sea ice area decreases in CESM1(CAM5) Increase in the rate of change of freshwater input required to offset decreasing sea ice area agrees with observed ice shelf melt increases